Implementasi Linier Programming Modelling untuk Maksimasi Profit Penjualan Produk Seblak pada UD. XYZ di Aceh Barat - Arrazy Elba Ridha; Ulfa Syahputri; Habib Satria; Adib Adib; Fuad Dwi Hanggara; Rizki Agam Syahputra; Abdiel Khaleil Akmal (Universitas Teuku Umar, 2023)
Seblak is a food that has seen an increase in demand in recent years, and is a promising culinary business that can be run with a small capital. UD. XYZ is a seblak business that started selling seblak in early 2022 in West Aceh and wants to maximize the profits from its seblak sales. One method that can do this is Linear Programming, which can determine decision-making that can group limited materials or resources to achieve an optimal or best solution. From UD. XYZ's weekly sales data, it can be transformed into a mathematical model that helps to find the maximum function of the profit from seblak sales. The linear programming calculation process in this study uses the Lingo 18.0 software to solve linear programming problems, which will be continued with the linear graph visualization of the objective function with the MATLAB software. The results of the study show that the maximum profit that will be obtained by UD. XYZ in one week is Rp. 420,000/week, this profit is already categorized as net profit that can be used for the development of UD. XYZ's seblak business. Of the three variables X1 (seblak noodles and crackers), X2 (seblak eggs), and X3 (seblak chicken/feet), variables X1 and X2 have the potential to increase maximum profit if increased. In this study, the objective point is also on the point axis (X1=0, X2=0, and X3 = 175).